PENGARUH KONSUMSI MENTIMUN TERHADAP STABILISASI TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DESA PANAIKANG KECAMATAN PATTALLASSANG KABUPATEN GOWA - Amriati Mutmainna; Darwis Darwis; Wa Mina La Isa; Ernawati Ernawati; Rusni Mato; M. Askar M. Askar; Hatma Hatma; Muzakkir Muzakkir (Media Keperawatan:Politeknik Kesehatan Makassar, 2022)
Background Hypertension is known by the general public as "high blood pressure" because this condition does indicate high blood pressure. Data from the World Health Organization (WHO) in 2018 shows that around 1.13 billion people in the world have hypertension, meaning that 1 in 3 people in the world is diagnosed with hypertension. The number of people with hypertension continues to increase every year, it is estimated that by 2025 there will be 1.5 billion people affected by hypertension, and it is estimated that every year 10.44 million people die from hypertension and its complications. Indonesia is 31.7% which means almost 1 in 3 populations aged 18 years and over suffers from hypertension, so it is necessary to have herbal handlers to stabilize pressure, one of which is by consuming cucumber juice. The purpose of this study was to determine the effect of cucumber juice in stabilizing blood pressure in patients with hypertension. Methods The methodology in this study uses quantitative research with a quasi-experimental approach with a one control group design with a sample size of 46. The sampling technique in this study uses random sampling using the Wilcoxon test. Result  The results showed that the mean diastolic blood pressure before administration of cucumber consumption therapy was 93.48 while the post-test mean value obtained was 90.87, the post-test median value was 90.97. Conclusion The results showed that there was an effect of cucumber consumption on the stability of diastolic blood pressure in patients with hypertension